The American Punitive Damages Law System for Ecological and Environmental Damage and its Implications for China - Mao, Xuhang; Wu, Jingyi (International Journal of Social Sciences and Public Administration, 2025)
The punitive damages system is a significant feature of American private law. The primary reason for its widespread acceptance in the United States is that it imposes certain limitations on punishing malicious crimes and also promotes the civil public interest litigation system and the jury system. To better leverage the punitive and deterrent effects of the punitive damages system against malicious acts, states across the U.S. have imposed varying degrees of restrictions on application conditions, proof standards, judicial review, compensation amounts, and distribution of damages. In order to transcend the limitations of traditional judicial review, the U.S. Supreme Court has established a clear set of criteria for unconstitutional determinations in punitive damages cases. Although there are considerable differences between American legislation and case law and those in many other aspects, relevant laws and precedents provide valuable references for Chinas development.